Not for sale : the return of the global slave trade--and how we can fight it - Batstone, David B., 1958- (New York : HarperOne, 2010)
"Award-winning journalist David Batstone reveals the story of a new generation of 21st century abolitionists and their heroic campaign to put an end to human bondage. In his accessible and inspiring book Not for Sale, Batstone carefully weaves the narratives of activists and those in bondage in a way that not only raises awareness of the modern-day slave trade, but also serves as a call to action. 2007 brought the 200th anniversary of the climax of the 19th century abolitionist movement, and inspired the world to pay tribute to great visionary figures such as William Wilberforce of the United Kingdom and American Frederick Douglass for their remarkable strides toward framing slavery as a moral issue that people of good conscience could not tolerate. This anniversary serves not only as a commemorative date for battles won against slavery, but also as a reminder that slavery and bondage still persist in the 21st century. An estimated 27 million people around the globe suffer in situations of forced labor and commercial sexual exploitation from which they cannot free themselves. Trafficking in people has become increasingly transnational in scope and highly lucrative. After illegal drug sales and arms trafficking, human trafficking is today the third most profitable criminal activity in the world, generating $31 billion annually. As many as half of all those trafficked worldwide for sex and domestic slavery are children under 18 years of age"--
Includes bibliographical references (p. [277]-281).
Keywords: Human trafficking; Slavery; Forced labor; Enslaved children